PERENCAAN PEMBUATAN MEDIA PEMBELAJARAN PERMUKAAN BUMI BERBASIS WEB DI SD NEGERI SUMBER 1 SURAKARTA - Retnoningsih, Dwi; Charolina, Astri; Nuro, Wayastahty (JURNAL GAUNG INFORMATIKA, 2015)
Learning media used for teaching in SD Negeri Sumber 1 Surakarta by the teachers is still conventionally done which are using lectures, and props with the globe. So the students still find it hard to understand the topic, such as the difficulty to distinguish between the bay with a cape. Web-based learning media is an alternative  method for interactive learning. The students will be more engaged when assisted with a number of media that supports the interaction process that is being implemented within the capturing of the educational messages conveyed by presenting interesting teaching materials such as the usage of pictures, animation, and video to actively participate in the learning process. The planning of this research is to develop learning media about Earthâs surface using PHP programming language and MySQL database. This design of thisapplication is using UML. The study was conducted using the methodology, ie observation, interview and references. Waterfall method is used as applicationdevelopment method. The testing method used in this research is the Black Box method. The test result indicates that the system is running well.